OP0268 Prediction of Cardiac and Vascular Events in Systemic Sclerosis: Input from Endothelin-1 Type A Receptor Antibodies. (10th June 2014) - Avouac, J.; Riemekasten, G.; Meune, C.; Ruiz, B.; Allanore, Y.
Abstract : Background: Cardiac and peripheral microvascular alterations are key features of systemic sclerosis (SSc). We have previously reported that angiogenic markers can predict the cardiovascular outcomes in SSc [1]. In parallel, a cross-sectional study reported an association between severe cardiovascular complications and functional antibodies against angiotensin II type 1 receptor (AT1 R) and Endothelin-1 type A receptor (ETA R) [2]. Objectives: Our aim was to investigate the respective merit of all these markers in a prospective cohort. Methods: Serum levels of anti-AT1 R and anti-ETA R autoantibodies, placenta growth factor (PlGF) and soluble vascular adhesion molecule (sVCAM) were measured with sandwich ELISA in a prospective cohort of 75 SSc patients. Circulating endothelial progenitor cells (EPCs) were quantified in peripheral blood by flow cytometry after cell sorting. The occurrence of at least one cardiac/vascular event was assessed during a planed 3-year follow-up by a composite index defined by the occurrence of at least one of the following event: a) one or more new ischemic digital ulcer (DU), b) pre-capillary pulmonary hypertension (PH) confirmed by right heart catheterization, c) left ventricular (LV) dysfunction, defined by a LV ejection fraction (EF)<50%, d) scleroderma renal crisis (SRC) (1). Results: The mean age of SSc patients (64 women) was 55±12 year old and the mean disease duration was 9±8 years at baseline. Twenty-eight patients developed at least one cardiac/vascular event (DU in 18, PH in 5, LV dysfunction in 4 and SRC in a single patient). By univariate analysis, high baseline serum levels of anti-ETA R were predictive of the occurrence of cardiac/vascular events (p=0.002), together with low EPC counts (p=0.003) and increased levels of PlGF (p=0.0005) and sVCAM (p=0.009). No predictive value of anti-AT1 R antibodies was identified. Multivariate analysis confirmed high serum levels of anti-ETA R antibodies (hazard ratio, HR: 3.71, 95%CI 1.44-9.52, p=0.03) and PlGF (HR: 5.22, 95%CI 1.96-15.87) as independent predictors of further development of cardiac/vascular events. The combination of high serum levels of anti-ETA R antibodies and PlGF was highly predictive of cardiac and vascular events occurrence during follow-up (HR 7.27 95%CI 2.49-23.51, P=0.0002). Conclusions: This study identifies for the first time anti-ETA R antibodies as an independent predictor of cardiac and vascular events in SSc. This functional antibody, together with other angiogenic markers and in particular PlGF, may serve as biomarkers to improve cardiovascular risk stratification and therefore allow earlier therapeutic intervention. References: Avouac et al, Ann Rheum Dis 2012. Riemekasten et al, Ann Rheum Dis 2011. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3482